Soil dynamics and earthquake engineering : proceedings of sessions of GeoShanghai 2010, June 3-5, 2010, Shanghai, China - Huang, Maosong; Yu, Xiong, 1974-; Huang, Yu, 1973- (American Society of Civil Engineers, 2010)
Proceedings of sessions of GeoShanghai 2010, held in Shanghai, China, June 3-5, 2010. Hosted by Tongji University, China; Shanghai Society of Civil Engineering, China; Chinese Institution of Soil Mechanics and Geotechnical Engineering, China. In cooperation with Alaska University Transportation Center, USA; Geo-Institute of ASCE, USA; Deep Foundation Institute, USA; East China Architectural Design and Research Institute Company, China; Georgia Institute of Technology, USA; Nagoya Institute of Technology, Japan; Transportation Research Board, USA; University of Newcastle, Australia; University of Illinois at Urbana-Champaign, USA; University of Kansas, USA; University of Tennessee, USA; Vienna University of Natural Resources and Applied Life Sciences, Austria. This Geotechnical Special Publication contains 42 papers that examine a variety of topics in soil dynamics and earthquake engineering. Topics include: dynamic soil-structural interactions under seismic loads; dynamic properties of soils and rocks; and seismic zoning and earthquake hazard assessment. Papers cover important issues such as the dynamic responses of earth dams, piles and pile groups, soil nailing, tunnels, landfills, and shallow foundations.
Keywords: Soil dynamics -- Congresses.; Earthquake engineering -- Congresses.; Engineering geology -- Congresses.; Soil-structure interaction -- Congresses.; elektronické knihy; electronic books